2001
DOI: 10.2519/jospt.2001.31.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Demographic Factors Affecting Distance Hopped and Limb Symmetry Index for the Crossover Hop-for-Distance Test in High School Athletes

Abstract: Bryce W Gaunt, P7; SCS, CSCS1David 7: Curd, MS2Study Design: Prospective cohort study using a random selection from an accessible population. Objectives: We examined anthropometric and demographic characteristics affecting distance hopped (DH) and limb symmetry index (LSI) in the crossover hop-for-distance test in uninjured high school athletes. Background: Between-subject comparisons of hop test results described by DH and LSI are common in the literature and clinical practice. The effect that anthropometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…While we classified limb dominance in control subjects according to self-report of which lower extremity each subject would use to kick a ball, 10,18 other authors have identified limb dominance according to actual performance during the physical test, so that LSI in asymptomatic subjects is (actual weak limb/actual strong limb) × 100. 1,8 A post hoc analysis (data not shown) using this latter method for calculating LSI values in control group subjects did not change our results. Mann-Whitney U tests still revealed that subjects with PFPS exhibited significantly lower LSI values than asymptomatic subjects (hip abduction, P = .015; hip extension, P,.001; hip external rotation, P = .009).…”
Section: Results Dmentioning
confidence: 65%
See 1 more Smart Citation
“…While we classified limb dominance in control subjects according to self-report of which lower extremity each subject would use to kick a ball, 10,18 other authors have identified limb dominance according to actual performance during the physical test, so that LSI in asymptomatic subjects is (actual weak limb/actual strong limb) × 100. 1,8 A post hoc analysis (data not shown) using this latter method for calculating LSI values in control group subjects did not change our results. Mann-Whitney U tests still revealed that subjects with PFPS exhibited significantly lower LSI values than asymptomatic subjects (hip abduction, P = .015; hip extension, P,.001; hip external rotation, P = .009).…”
Section: Results Dmentioning
confidence: 65%
“…1 In asymptomatic subjects the formula for calculating the LSI is: (performance in the nondominant, assumed-weak limb/performance in the dominant, assumed-strong limb) × 100. 1,8,10,18 A lower LSI value indicates decreased function in the symptomatic (subjects with PFPS) or nondominant (asymptomatic subjects) limb.…”
Section: 726mentioning
confidence: 99%
“…LSI is a percentile measurement comparing the limb symmetry of the affected side to the unaffected side. Figure 2 shows the calculation for LSI [45].The LSI has been utilized as a quantitative measure to determine the strength and performance of an athlete prior to return to sport [46][47][48]. Non-injured athletes have a LSI of 90-95% [49], while individuals who suffer an ACL injury rarely reach greater than 90% LSI post reconstruction [50].…”
Section: Limb Symmetry Indexmentioning
confidence: 99%
“…Both the absolute hop distance and the LSI are valuable functional performance outcomes 13 . However, since hop length improves with age during childhood due to growth, 15 normalizing hop performance to body height may also be relevant when evaluating hop performance in ACL‐injured children 16 .…”
Section: Introductionmentioning
confidence: 99%